Using a novel approach to determine the pore pressure of West Qurna 15 oil well in South of Iraq (Journal of Engineering, 2020)
Pore pressure means the pressure of the fluid filling the pore space of formations. When pore pressure is higher than hydrostatic pressure, it is named abnormal pore pressure or overpressure. When abnormal pressure occurred leads to many severe problems such as well kick, blowout during the drilling, then, prediction of this pressure is crucially essential to reduce cost and to avoid drilling problems that happened during drilling when this pressure occurred. The purpose of this paper is the determination of pore pressure in all layers, including the three formations (Yamama, Suliay, and Gotnia) in a deep exploration oil well in West Qurna field specifically well no. WQ-15 in the south of Iraq. In this study, a new approach of mechanical specific energy (MSE) was used to predict the pore pressure of the deep well WQ-15, and compare the results obtained with the previous techniques Magara, Eaton, Equivalent Depth and Sigma log along with the actual pore pressure using a statistical equation of Absolute Average Percentage Error (AAPE). The newly suggested approach obtained is good, and accepted results of pore pressure are encouraging to be applied in other oil wells rather than depending on previous traditional methods, especially when well logs are unavailable.